CANNING OF SMOKED SARDINE. - NAIR, T. S UNNIKRISHNAN; BALACHANDRAN, K K; MADHAVAN, P (Fishery Technology, 2017)
A process for canning smoked oil sardine (Sardinella longiceps) is described. Cold blanching of dressed fish in brine, smoking followed by drying in hot air or cooking in steam to reduce the moisture content to the required level and subsequent canning yields product with good organoleptic properties. Coconut husk is used as source of smoke.